From molecule to oblivion: dedicated brain circuitry underlies anesthetic loss of consciousness permitting pain-free surgery - Baron, Mark; Devor, Marshall (Frontiers in Molecular Neuroscience, 2023)
The canonical view of how general anesthetics induce loss-of-consciousness (LOC) permitting pain-free surgery posits that anesthetic molecules, distributed throughout the CNS, suppress neural activity globally to levels at which the cerebral cortex can no longer sustain conscious experience. We support an alternative view that LOC, in the context of GABAergic anesthesia at least, results from anesthetic exposure of a small number of neurons in a focal brainstem nucleus, the mesopontine tegmental anesthesia area (MPTA). The various sub-components of anesthesia, in turn, are effected in distant locations, driven by dedicated axonal pathways. This proposal is based on the observations that microinjection of infinitesimal amounts of GABAergic agents into the MPTA, and only there, rapidly induces LOC, and that lesioning the MPTA renders animals relatively insensitive to these agents delivered systemically. Recently, using chemogenetics, we identified a subpopulation of MPTA “effector-neurons” which, when excited (not inhibited), induce anesthesia. These neurons contribute to well-defined ascending and descending axonal pathways each of which accesses a target region associated with a key anesthetic endpoint: atonia, anti-nociception, amnesia and LOC (by electroencephalographic criteria). Interestingly, the effector-neurons do not themselves express GABAA-receptors. Rather, the target receptors reside on a separate sub-population of presumed inhibitory interneurons. These are thought to excite the effectors by disinhibition, thus triggering anesthetic LOC.